By nightfall - Cunningham, Michael 1952- (New York Farrar, Straus and Giroux, 2010)
Peter and Rebecca Harris--mid-forties denizens of Manhattan's SoHo, he a dealer, she an editor--are admirable, enviable contemporary urbanites with every reason, it seems, to be happy. Then Rebecca's much younger look-alike brother, Ethan (known in the family as Mizzy, "the mistake"), shows up for a visit
Keywords: Art dealers -- New York (State) -- New York -- Fiction; Brothers and sisters -- Fiction